Effect of Microinjection of Cryoprotective Agents on Survival of Misgurnus Fossilis L. Loach Embryos, 1758 - Mikson, K. B.; Kopeyka, Ye. F.; Grischenko, V. I. (Problems of Cryobiology and Cryomedicine, 2008)
Investigated survival rate of loach embryos at a stage late epibole after a microinjection of DMSO, PEG-100, PEG-1500 and formamide (FA) cryoprotectants in area of perivitelline spaces (PS) and yolk sac (YS). It is established that at introduction of DMSO, PEG-100 and PEG-1500 in concentration of 10, 50 and 95 % in area of PS and at the subsequent 30-minute incubation in 0,88 and 0,29 M to sucrose, survival rate level decreased: 58,4–48,5, 74,4–53,9 and 79,63–59,6 % accordingly. At FA survival rate level under the same conditions decreased from 7 to 3,6 %. At introduction of PEG-100 and PEG-1500 in concentration 10, 50 and 95 % in YS area at 30-minute incubation in 0,88 and 0,29 M to sucrose level of survival rate had no statistically significant differences and was higher, than at introduction of DMSO and FA.